Implementation of Multi Criteria Decision Making In The Evaluation Of The Work Of FKIP UHN Lecturers - simanjuntak, ruth mayasari (UIN Sumatera Utara, 2023)
The purpose of this study is to implement the multi criteria decision making (MCDM) with the Analytical Hierarchy Process (AHP) method to obtain the results of the assessment of the performance of the lecturer in determining the best lecturer. The use of this method begins with creating a hierarchical structure of the problem to be studied. A matrix of pairs of comparisons will be searched for the weight of each criterion by normalizing the average of the opinion of the respondent. Maximum eigen values and normalized eigen vectors will be obtained from the matrix. In the process of determining the hierarchical weighing factor, the competence test should be performed CR< 0,1. The factor variables used are student questionnaires towards learning (C1), Research (C2), Commitment to the community (C3), and Seminar/Workshop/General College/recognition (C4). Based on the data processing results, the priority is Research criteria (C2) of 0.318505; then the second criterion is Student questionnaire towards learning(C1) of 0.287053; the third is Abdimas’s (C3) criteria of 0.237667 and the last is the Seminar/workshop/general class/recognitive (C4) of 0.156775. And based on analysis using Analytical Hierarchy Process (AHP) then who becomes the best lecturer in the Faculty of Education and Sciences of the University of HKBP Nommensen is initially D15 set as the best faculty in position 1 with a score of 0.35 or 35%, D 14 is in position 2 with a rating of 0.335 or 33.5% and D12 is in the third position with the score of 0,325 or 32.5%.